The boy who bit Picasso - Penrose, Antony; Picasso, Pablo, 1881-1973. (London : Thames & Hudson, 2011)
Antony Penrose describes his boyhood friendship with artist Pablo Picasso, whom he met when his parents entertained the artist at their home in England.
Publisher's Weekly
2.9
K-3
K-3
Keywords: Artists -- France -- Biography -- Anecdotes -- Juvenile literature; Penrose, Antony -- Anecdotes -- Juvenile literature; Picasso, Pablo, -- 1881-1973 -- Anecdotes -- Juvenile literature; Picasso, Pablo, -- 1881-1973 -- Friends and associates -- Juvenile literature; Penrose, Antony; Picasso, Pablo, -- 1881-1973.; Penrose, Antony -- Anecdotes; Picasso, Pablo, -- 1881-1973 -- Anecdotes; Picasso, Pablo, -- 1881-1973 -- Friends and associates; Artists; Artists -- France -- Biography -- Anecdotes